O-057 The pregnant outcome after laparoscopy treatment for subtle distal fallopian tube abnormalities in infertile population: a prospective cohort study. (30th June 2022) - Zheng, X; Yu, X; He, C; Hongjing, H; Jing, G
Abstract: Study question: What is the the pregnancy outcome after laparoscopy treatment for subtle distal fallopian tube abnormalities and the factors related with natural pregnancy. Summary answer: The natural pregnancy rate is 46.58% after laparoscopy and patients' age, duration time of infertility and concurrent number of abnormalities are related with natural pregnancy. What is known already: Subtle distal fallopian tube abnormalities are a group of diseases that are characterized by subtle variations in tubal anatomy including fimbrial agglutination, tubal diverticula, accessory ostium, fimbrial phimosis, and accessory fallopian tube. The prevalence of subtle distal fallopian tube abnormalities is high in infertile women.This group of diseases is highly related to endometriosis, especially its early stage, and may indicate fimbrial abnormalities in endometriosis. Study design, size, duration: This was a prospective cohort study conducted in the Reproductive Medicine Center of an university-affiliated teaching hospital from January 2017 to December 2018. Participants/materials, setting, methods: 234 patients with subtle distal fallopian tube abnormalities were included. Laparoscopies were performed by four senior reproductive surgeons who were familiar with the diagnostic criteria and surgery treatment for subtle abnormalities. The fallopian tube abnormalities were corrected and endometriosis was treated by either electrical ablation for peritoneal lesions or endometrioma excision.The participants were followed up by phone every 12 months for pregnancy outcome until 36 months after surgery. Main results and the role of chance: 167 patients conceived after surgery(clinical pregnancy rate 71.37%). 109 patients conceived naturally (natural pregnancy rate 46.58%) and 59 patients conceived after in IVF（One case conceived naturally after live birth after IVF, four cases conceived naturally twice) . The average time for natural conception after surgery is 8.36±7.47 months. 51.4% of natural pregnancy occurred within 6 months and 79.8% occurred within 12 months.Among the 109 naturally conceived patients, there were 94 cases of live birth, 13 cases of natural abortion (natural abortion rate 11.92%) and 2 cases of ectopic pregnancy (ectopic pregnancy rate 1.83%). No preterm birth, multiple pregnancy or birth defects were reported in this group.The patient age(HR = 0.917, 95%CI 0.870-0.917, P=0.001), duration of infertility(HR = 0.846, 95%CI 0.740-0.966, P=0.014) and concurrent number of subtle abnormalities (HR = 0.636, 95%CI 0.416-0.970, P=0.036) are the factors associated with natural pregnancy. The type of subtle abnormalities, type of infertility, body mess index, concurrent endometriosis, uterine cavity abnormalities and myoma are not related with natural pregnancy. Limitations, reasons for caution: Not all kinds of subtle distal abnormalities are included such as paratubal cyst is excluded from the study. Not all the patients had the test of ovarian reserve such as AMH, antral follicle count and FSH level, so we couldn't evaluate the relationship between ovarian reserve and natural pregnancy. Wider implications of the findings: This is the largest clinical study that investigated the pregnancy outcome of subtle fallopian tube abnormalities in the infertile population.Laparoscopy surgery is an effective treatment for infertility patients with subtle distal fallopian tube abnormalities, especially for the young, short duration time of infertility and ≤2 types of subtle abnormalities. Trial registration number: ChiCTR2000029095